Case report of COVID‐19 in a kidney transplant recipient: Does immunosuppression alter the clinical presentation?. Issue 7 (9th April 2020) - Guillen, Elena; Pineiro, Gaston J.; Revuelta, Ignacio; Rodriguez, Diana; Bodro, Marta; Moreno, Asunción; Campistol, Josep M.; Diekmann, Fritz; Ventura‐Aguiar, Pedro
Abstract : COVID‐19 is novel infectious disease with an evolving understanding of its epidemiology and clinical manifestations. Immunocompromised patients often present atypical presentations of viral diseases. Herein we report a case of a COVID‐19 infection in a solid organ transplant recipient, in which the first clinical symptoms were of gastrointestinal viral disease and fever, which further progressed to respiratory symptoms in 48 hours. In these high risk populations, protocols for screening for SARS‐Cov2 may be needed to be re‐evaluated. Abstract : The authors report an atypical presentation of COVID‐19 infection in a kidney transplant recipient, demonstrating the relevance of screening in a high risk population.